On the Parable of the Management Scholars and the Russia–Ukraine War. (17th July 2022) - Aguinis, Herman; Cope, Amando; Martin, Ursula M.
Abstract: We invoke the parable of "the blind men [sic] and the elephant" to argue that conflicting perspectives from scholars across management subfields preclude a comprehensive understanding of the Russia–Ukraine war. To address this problem, we argue for the need to develop programmatic theories that provide better explanations and predictions and guide empirical research by adopting multilevel and multimethod approaches.